(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The present paper focuses on Family dynamics and its impact on present generation in novels of Sudha Murthy. The novels written by Sudha Murthy depict the lives of city technocrats who succumb to status and consumerism. They fail to live life in its true meaning because existence is like a battle. Her female protagonists are also notably intelligent, determined, and steadfast. They are the real Indian women, not the stereotypical, helpless women we frequently see in movies or books. Fragments from within one's own family when wealth and power triumph. Girls are the silent victims in business families because they always sacrifice their own goals and ambitions for their husbands' success. Innovative Indian author Sudha Murthy focuses on practical issues that women face in contemporary society in her novel gently Falls The Bakula. She discusses man-woman relationships and how a single-minded partner's ambition can harm a well-managed relationship. This paper examines the knowledgeable woman's role as a wife in a love marriage, her submissive life as she struggles with loneliness and becomes submissive to her husband's egotistical tendencies in order to comprehend her freedom as an independent woman. Through Shrimathi and Shrikant, Murthy puts the marginalization of Indian women in the hands of their husbands.